Phenotypic antibiotic susceptibility testing of pathogenic bacteria using photonic readout methods: recent achievements and impact - Tannert, Astrid; Grohs, Richard; Popp, Juergen; Neugebauer, Ute (Applied Microbiology and Biotechnology, 2019)
The development of antibiotic resistances in common pathogens is an increasing challenge for therapy of infections and especially severe complications like sepsis. To prevent administration of broad-spectrum and potentially non-effective antibiotics, the susceptibility spectrum of the pathogens underlying the infection has to be determined. Current phenotypic standard methods for antibiotic susceptibility testing (AST) require the isolation of pathogens from the patient and the subsequent culturing in the presence of antibiotics leading to results only after 24–72 h. Since the early initialization of an effective antibiotic therapy is crucial for positive treatment result in severe infections, faster methods of AST are urgently needed. A large number of different assay systems are currently tested for their practicability for fast detection of antibiotic resistance profiles. They can be divided into genotypic ones which detect the presence of certain genes or gene products associated with resistances and phenotypic assays which determine the effect of antibiotics on the pathogens. In this mini-review, we summarize current developments in fast phenotypic tests that use photonic approaches and critically discuss their status. We further outline steps that are required to bring these assays into clinical practice.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Fluorescence; IR; Microscopy; Raman; Rapid susceptibility test; Scattering; Spectroscopy